Unicentric Castleman disease presenting as a retroperitoneal peripancreatic mass: A report of two cases and review of literature - Cheng, Jia-Lin (World J Gastroenterol, 2018)
Castleman disease (CD) is a rare disorder of lymph nodes and related tissues. CD generally occurs in the mediastinum, as well as in cervical, retroperitoneal and axillary regions. The disease is classified into two major types: unicentric CD (UCD) and multicentric CD. The occurrence of UCD in the retroperitoneal peripancreatic region is quite rare. We encountered two cases of retroperitoneal peripancreatic UCD in our hospital during the past three years. Following a series of medical examinations, including magnetic resonance imaging, computed tomography, ultrasonography and postoperative histopathological examination, these two patients were diagnosed with UCD, which presented as a retroperitoneal peripancreatic mass. The mass in each patient was completely excised, and no postoperative radiochemotherapy was administered. Both patients recovered well without recurrence during a follow-up period of 30 mo and 8 mo.